2020
DOI: 10.1039/d0ra00562b
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical grafting of poly(glycidyl methacrylate) on a carbon-fibre surface

Abstract: In this work, glycidyl methacrylate (GMA) was polymerised and grafted onto the surface of carbon fiber (CF) by using electrochemical grafting to improve the interfacial properties between the fibre and epoxy resin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Reactive CE compatibilizers significantly improve the toughness and elongation at the break of the PLA-based blends, which was already confirmed by many studies [18,[29][30][31][32]. Interestingly, the addition of reactive compatibilizers also improves the fiber-matrix interface interactions for composites [33,34], especially for materials with the addition of the lignocellulosic fillers [35,36]. Our previous research on PLA/PBAT systems aimed to indicate the improvement of wettability of flax fibers with the addition of CE [37].…”
Section: Introductionsupporting
confidence: 53%
“…Reactive CE compatibilizers significantly improve the toughness and elongation at the break of the PLA-based blends, which was already confirmed by many studies [18,[29][30][31][32]. Interestingly, the addition of reactive compatibilizers also improves the fiber-matrix interface interactions for composites [33,34], especially for materials with the addition of the lignocellulosic fillers [35,36]. Our previous research on PLA/PBAT systems aimed to indicate the improvement of wettability of flax fibers with the addition of CE [37].…”
Section: Introductionsupporting
confidence: 53%
“…42 Second, polymer chains can be initiated from active sites on carbon fiber and grown in the presence of hardeners (Figure 7). 44 Hu et al 45 used click chemistry to graft GMA onto carbon fiber surface via electrochemical grafting. Once the chain-growth polymerization of methacrylates to generate p(GMA) is completed, a second polymerization step (i.e., step-growth polymerization) will be activated to form 3D cross-linked polymer matrix by enabling the formation of covalent bonds between the epoxide group of poly(GMA) chains and amine groups of hardeners.…”
Section: T H Imentioning
confidence: 99%
“…A high voltage or current needs to be set in the experiment to make the carbon fiber reach the required reaction conditions and the ideal grafting effect, which can easily destroy the surface structure of the carbon fiber. , Researchers in the field of galvanic corrosion found that the electrode potential of materials can be changed through the galvanic coupling effect when two different materials are used together. Wielage indicated that when carbon fiber and aluminum were in contact in an electrolyte, the carbon fiber with a higher electrode potential became the cathode and polarized, decreasing the electrode potential of the carbon fiber. Hu applied the above principles to the electrochemical grafting of poly­(glycidyl methacrylate) on the carbon fiber surface using aluminum and carbon fiber together as electrodes, finding that the grafting rate of the carbon fiber was improved. But there are many problems yet to be solved.…”
Section: Introductionmentioning
confidence: 99%